2011
DOI: 10.1177/0310057x1103900216
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Human Cultured Myotubes Responses Mediated by Ryanodine Receptor 1

Abstract: Malignant hyperthermia is a life-threatening condition caused by autosomal dominant mutations in the ryanodine receptor type 1 gene. Identifying patients predisposed to malignant hyperthermia is done through the Ca-induced Ca release test in Japan. We examined the intracellular calcium concentration in human cultured muscle cells and compared the sensitivity of myotubes to ryanodine receptor type 1 activators based on the Ca-induced Ca release rate. We assessed the utility of this method as an identifying test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 38 publications
(78 reference statements)
1
2
0
Order By: Relevance
“…However, the CICR rate test can reveal abnormalities associated with Ca 2+ release from the SR, a process mainly controlled by RYR1 in skeletal muscle. 9 The EC 50 values of 4CmC and caffeine in participants with accelerated CICR rates in this study were lower than the previously reported cut-off values to diagnose MH, 9 which confirmed that the participants in this study had MH predisposition. The RYR1 variants identified in this study are shown in Table 1.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…However, the CICR rate test can reveal abnormalities associated with Ca 2+ release from the SR, a process mainly controlled by RYR1 in skeletal muscle. 9 The EC 50 values of 4CmC and caffeine in participants with accelerated CICR rates in this study were lower than the previously reported cut-off values to diagnose MH, 9 which confirmed that the participants in this study had MH predisposition. The RYR1 variants identified in this study are shown in Table 1.…”
Section: Discussionsupporting
confidence: 82%
“…As described previously, 9 myoblasts were obtained from the surplus muscle pieces after CICR examination and cultured in Dulbecco’s modified Eagle’s medium and F12 medium (DMEM/F12; Invitrogen, Carlsbad, CA, USA) supplemented with 10% heat-inactivated fetal bovine serum (FBS; Sigma–Aldrich, St Louis, MO, USA). The myoblasts were then frozen and stored at –70°C.…”
Section: Methodsmentioning
confidence: 99%
“…The isometric tension was measured using a force transducer to determine the CICR rate. MH predisposition was achieved if CICR was increased and defined as a CICR rate > two standard deviations (SD) above the mean of the control (IVCT and CHCT negative) [16] CICR values [17,18].…”
Section: Cicr Rate Testmentioning
confidence: 99%